STRATEGI MEMPERTAHANKAN KEARIFAN LOKAL PETANI PADI SAWAH DI DESA BUNGARAYA KECAMATAN BUNGARAYA KABUPATEN SIAK - Damanik, Chandra Saputra; ', Cepriadi; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this observation is to explain local wisdom (ritual and myth) that existed in the agricultural environment of paddy and formulating strategies in maintaining local knowledge of agricultural environment of paddy in the village of Bungaraya sub Bungaraya district of Siak. The method used in this research is descriptive qualitative and SWOT with a sampling technique that uses snowball sampling technique or performed in sequence to ask for information on people who have been interviewed. The number of samples in this study is 13 samples. The analysis is used qualitative data analysis. Research shows that local knowledge rice farmers that once existed in the village of Bungaraya sub Bungaraya numbered 61 local wisdom. Local wisdom of rice farmers who still exist in the village Bungaraya sub Bungaraya numbered 19 local wisdom,local knowledge is still preserved farmers because of the tradition that can not be abandoned and still profitable. Keywords: Local Wisdom, Paddy, Ritual, Myth